A206 SUSCEPTIBILITY OF HNF4AΔIEC MICE TO SALMONELLA INFECTIONS. (26th February 2020) - Pupo Gómez, D; Reyes-Nicolas, V; Marrero, G; Perreault, N; Menendez, A; Boudreau, F
Abstract: Background: Inflammatory bowel diseases (IBD) are a group of chronic disorders that affect more than 233 000 Canadians and for which there is not yet an effective treatment. In addition, IBD is a multifactorial disease depending on genetic, immune and environmental dysregulations. The gastrointestinal epithelium plays an important role as a barrier that protects against antigens and bacterial products that are in the lumen. It is well recognized that a defect in the integrity of the barrier and its functions may be involved in the development of these diseases. On the other hand, our laboratory has shown that the conditional deletion of HNF4alpha nuclear receptor (Hnf4a) in the intestinal epithelium of mice can lead to the development of chronic inflammation of the intestine. However, the impact of the loss of this transcriptional factor on the epithelial barrier is still controversial. Aims: To evaluate the impact of Hnf4a deletion on the epithelial barrier during bacterial infections. Methods: We used a tamoxifen-inducible Cre-loxP system to delete the Hnf4a gene in the intestinal epithelium of 2-month-old mice, that were then infected with an attenuated strain of Salmonella typhimurium (SB1003) during 4 days. S. typhimurium loads were determined in cecum and colon content, and in liver, spleen tissues by plating homogenates on LB agar supplemented with streptomycin. Also, histological examinations and gene expression of selected targets were assessed between mutant (Hnf4aΔIEC) and control mice. Results: The tamoxifen-inducible Cre-loxP system was able to delete intestinal Hnf4a gene expression with almost 100% of efficacy. Analysis by qPCR showed that the infection caused significant changes on the response of different infection responsive components ( Relmβ, Muc2 and IL-33 ) in mutant mice. In addition, morphological analyses revealed an increase in the infiltration of immune cells and the number of goblets cells, indicative of an increase in the susceptibility to Salmonella typhimurium (SB1003) infection of the mutant mice. Conclusions: Altogether, our results suggest that Hnf4a could be involved or play an important role as a modulator of the intestinal epithelial barrier function during Salmonella typhimurium (SB1003) infection. Therefore, understanding the mechanisms involved in this process could allow the development of better therapies for IBD. Funding Agencies: CIHR